Contribution of Electron Pressure to Ring Current and Ground Magnetic Depression Using RAM‐SCB Simulations and Arase Observations During 7–8 November 2017 Magnetic Storm. Issue 6 (21st June 2021) - Kumar, S.; Miyoshi, Y.; Jordanova, V. K.; Engel, M.; Asamura, K.; Yokota, S.; Kasahara, S.; Kazama, Y.; Wang, S.‐Y.; Mitani, T.; Keika, K.; Hori, T.; et al.
Abstract: Understanding the physical processes that control the dynamics of energetic particles in the inner magnetosphere is important for both space‐borne and ground‐based assets essential to the modern society. The storm time distribution of ring current particles in the inner magnetosphere depends strongly on their transport in the evolving electric and magnetic fields along with particle acceleration and loss. In this study, we investigated the ring current particle variations using observations and simulations. We compared the ion (H +, He +, and O + ) and electron flux and plasma pressure variations from Arase observations with the self‐consistent inner magnetosphere model: Ring current Atmosphere interactions Model with Self Consistent magnetic field (RAM‐SCB) during the 7–8 November 2017 geomagnetic storm. We investigated the contribution of the different species (ions and electrons) to the magnetic field deformation observed at ground magnetic stations (09°–45° MLat) using RAM‐SCB simulations. The results show that the ions are the major contributor with ∼88% and electrons contribute ∼12% to the total ring current pressure. It is also found that the electron contribution is non‐negligible (∼18%) to the ring current in dawn‐side during the main phase of the storm. Thus, the electron contribution to the storm time ring current is important and should not be neglected. Key Points: Ring current Atmosphere interactions Model with Self Consistent magnetic field (RAM‐SCB) reproduced the particle fluxes very well observed by Arase satellite in inner magnetosphere during November 2017 magnetic storm The ring current pressure distribution from RAM‐SCB in inner magnetosphere shows agreement with ground magnetic data The electron pressure contributed ∼18% to the dawn‐side ground magnetic depression after substorm injections